CHARACTERIZATION OF BODY COMPOSITION IN NORTH OF PARANÁ: LONGITUDINAL STUDY (Fiep Bulletin - online, 2020)
INTRODUCTION: Brazil lives with the nutritional transition, which is characterized by a reduction in malnutrition and an increase in obesity. OBJECTIVES: To perform a longitudinal analysis classifying the BMI of children and adolescents enrolled in the year 2014 to 2018 in the municipal schools of Jacarezinho, Cambará and Andirá - PR, characterizing their body composition, as well as the prevalence of malnutrition and childhood obesity, in order to support preventive health, social and cultural analyzes. METHODOLOGY: This is a longitudinal study of approximately 4,682 overweight (obese and overweight) children and adolescents from 2014 to 2018, in which body mass and height were evaluated. RESULTS: The highest percentage is eutrophic, however there is a prevalence of overweight and obesity according to the Cole method (2007), regarding malnutrition. Moreover, when the percentage of each city is observed, the city of Cambará presents a higher percentage in relation to the others, around 33%. CONCLUSION: There was an average increase in childhood obesity in relation to malnutrition in the cities of Jacarezinho, Cambará and Andirá - PR characterizing the nutritional transition. In addition, all cities when analyzed generally had an increase in childhood obesity over the years 2014 to 2018 and when analyzed only the city of Cambará, it has a percentage of 33% that is higher than expected by the World Health Organization.